The 17-kb Tam1 element of Antirrhinum majus induces a 3-bp duplication upon integration into the chalcone synthase gene - Bonas, Ulla (1984)
The DNA sequence of the termini and the flanking regions of the 17-kb transposable element Tam1 was determined. Tam1 is integrated in the chalcone synthase gene of the niv-53 mutant of Antirrhinum majus. The element has a 13-bp perfect inverted repeat at its termini and appears to induce a 3-bp duplication of the target site upon integration. The DNA sequence of a niv(+) revertant was analyzed and found to differ from the wild-type sequence by an additional 2 bp that seem to derive from the target site duplication. Stretches of homologous sequences have been found between the ends of Tam1, within each terminus of the element, and between the termini and target site sequences. Structural similarities between the ends of Tam1 and the Spm-18 element of Zea mays reflect a possible horizontal spread of a common progenitor.